2014
DOI: 10.1001/jama.2014.5613
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Tumor Necrosis Factor-α Antagonists and Risk of Cancer in Patients With Inflammatory Bowel Disease

Abstract: In this Danish nationwide study, exposure to TNF-α antagonists among patients with IBD was not associated with an increased risk of cancer over a median follow-up of 3.7 years among those exposed. An increased risk associated with longer-term accumulated doses and follow-up cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
158
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(172 citation statements)
references
References 29 publications
4
158
1
3
Order By: Relevance
“…The risk of cancer associated with methotrexate therapy has been assessed in patients with rheumatoid arthritis and most studies have not found an increased risk 22 In comparison, treatment with thio-purines increases the risk of lymphoma and nonmelanoma skin cancer. 3,[23][24][25] Nausea and vomiting were the most common minor adverse events associated with methotrexate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of cancer associated with methotrexate therapy has been assessed in patients with rheumatoid arthritis and most studies have not found an increased risk 22 In comparison, treatment with thio-purines increases the risk of lymphoma and nonmelanoma skin cancer. 3,[23][24][25] Nausea and vomiting were the most common minor adverse events associated with methotrexate therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of the biological development of solid tumors is not well characterized. Andersen et al (2014) showed no increased risk of solid cancer development in patients exposed to anti-TNF therapy, at a median follow-up of 3.7 years [13].…”
Section: Discussionmentioning
confidence: 92%
“…Lymphomas have also been reported in patients treated with anti-tumor necrosis factor-α (TNF-α) drugs, which could act by decreasing apoptosis and allowing proliferation of neoplastic cells [2] , but in most studies, anti-TNF-α appears to have no correlation with lymphomas [10] . In a register-based cohort study conducted by Nyboe Andersen et al [13] , 56,146 patients were included and 8 cases of lymphomas, with 2 HL, were diagnosed. There was a risk of 0.90 (95% CI, 0.42-1.91) for those who were under anti-TNF-α after adjusting the variable to the azathioprine use [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In a register-based cohort study conducted by Nyboe Andersen et al [13] , 56,146 patients were included and 8 cases of lymphomas, with 2 HL, were diagnosed. There was a risk of 0.90 (95% CI, 0.42-1.91) for those who were under anti-TNF-α after adjusting the variable to the azathioprine use [13] . Then, caution must be taken, when associating lymphomas with anti-TNF-α therapy.…”
Section: Discussionmentioning
confidence: 99%